Self-Harm Behavior pada Mahasiswa Keperawatan - Shafira, Ananda Nur; Hargiana, Giur (Jurnal Kesehatan, 2022)
The majority of college students are in the phase of emerging adulthood of human development. In this transition period, the students are susceptible to experiencing psychological instability due to many changes in their lives. Nursing students are presumed to be at risk of high-stress levels because of the high demands, expectations and activities during their study. Therefore, some students struggle to adapt to their college life and choose to avoid their responsibilities or make some dangerous decisions (self-harm behavior) as it is believed to be a form of coping mechanism to release their stress.  This study used a cross sectional approach with the aim of finding the prevalence of self-harm behavior among nursing students. This study involved 236 students from Faculty of Nursing, University of Indonesia with probability proportionate sampling technique. The instrument used is the modified Indonesian version of Self-Harm Behavior Questionnaire (SHBQ). The results showed that nursing students engaged in self-harm behavior, including self-harm (34.3%), suicide attempted (8.1%), suicide threat (7.2%), and suicide ideation (30.5%). The existence of prevalence of self-harm behavior among nursing students is needed to improve prevention and treatment at the university level.